Characteristics of healthcare organisations struggling to improve quality: results from a systematic review of qualitative studies. Issue 1 (25th July 2018) - Vaughn, Valerie M; Saint, Sanjay; Krein, Sarah L; Forman, Jane H; Meddings, Jennifer; Ameling, Jessica; Winter, Suzanne; Townsend, Whitney; Chopra, Vineet
Abstract : Background: Identifying characteristics associated with struggling healthcare organisations may help inform improvement. Thus, we systematically reviewed the literature to: (1) Identify organisational factors associated with struggling healthcare organisations and (2) Summarise these factors into actionable domains. Methods: Systematic review of qualitative studies that evaluated organisational characteristics of healthcare organisations that were struggling as defined by below-average patient outcomes (eg, mortality) or quality of care metrics (eg, Patient Safety Indicators). Searches were conducted in MEDLINE (via Ovid), EMBASE, Cochrane Library, CINAHL, and Web of Science from database inception through February 8 2018. Qualitative data were analysed using framework-based synthesis and summarised into key domains. Study quality was evaluated using the Critical Appraisal Skills Program tool. Results: Thirty studies (33 articles) from multiple countries and settings (eg, acute care, outpatient) with a diverse range of interviewees (eg, nurses, leadership, staff) were included in the final analysis. Five domains characterised struggling healthcare organisations: poor organisational culture (limited ownership, not collaborative, hierarchical, with disconnected leadership), inadequate infrastructure (limited quality improvement, staffing, information technology or resources), lack of a cohesive mission (mission conflicts with other missions, is externally motivated, poorly defined or promotes mediocrity), system shocks (ie, events such as leadership turnover, new electronic health record system or organisational scandals that detract from daily operations), and dysfunctional external relations with other hospitals, stakeholders, or governing bodies. Conclusions: Struggling healthcare organisations share characteristics that may affect their ability to provide optimal care. Understanding and identifying these characteristics may provide a first step to helping low performers address organisational challenges to improvement. Systematic review registration: PROSPERO: CRD42017067367.